Optimizing Physical Education Learning: Developing Local Wisdom-Based Learning Materials To Improve Students' Learning Motivation - Adrizal, Mohd.; Ilham, Ilham; Ali, Muhammad; Bangun, Sabaruddin Yunis; Sastradika, Dedi; Ockta, Yovhandra (STKIP Singkawang, 2024)
Local wisdom is a characteristic or specialty of a region that must be preserved. However, currently, the rapid development of technology has various impacts on life, especially the neglect of various games and cultures from a region. This study will develop local wisdom-based teaching materials in Physical Education and Sports subjects in Elementary Schools Implementing local wisdom-based learning in basic learning is an effort that can be used as a basis for building awareness of local culture. The method used is research and development (R&D) with a 4D design (Define, Design, Develop and Disseminate). The results of the Expert assessment show that Local Wisdom-based Teaching Materials are categorized as very good and feasible to be applied to learning. The results of the trial of local wisdom-based teaching module products show that the achievement of high learning motivation reaches 82.69% in every aspect of student learning motivation indicators. These results indicate that local wisdom-based teaching materials in PE subjects are feasible to use and further research can develop these teaching materials at the secondary education level